THE EFFECT OF VIRAL MARKETING AND SOCIAL MEDIA INSTAGRAM ON REPURCHASE INTEREST THROUGH CONSUMER TRUST AS AN INTERVENING VARIABLE - Alya Ananda Riel; Syahmardi Yacob; Ade Titi Nifita (JOURNAL OF BUSINESS STUDIES AND MANGEMENT REVIEW, 2022)
The purpose of this research is to determine the effect of; viral marketing on customer trust; viral marketing on consumer repurchase intention; customer trust on consumer repurchase intention; viral marketing on consumer repurchase intention through customer trust as an intervening variable. This study uses a quantitative descriptive method with a purposive sampling method of 200 respondents. This research data collection uses an online method to distribute questionnaires to respondents. This research data analysis method uses SmartPLS 3.0. The results from this study indicate that the viral marketing variable has a significant positive effect on consumer trust in Cake by Nadia consumers. The viral marketing variable has a significant positive effect on consumer repurchase intention in Cake by Nadia. The consumer trust variable has a significant positive effect on consumer repurchase intention in Cake by Nadia Consumers. Then, the viral marketing variable has a significant positive effect on consumer repurchase intention through consumer trust as an intervening variable on Cake by Nadia consumers.